Kanon Sastra Pendidikan untuk Pembelajaran Bahasa dan Sastra - Mohammad Fadli; Zainal Rafli; Syamsi Setiadi (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This article aims to discuss the canonization of literature in the field of education, especially language and literature teaching. The research method is literature study which is used to discuss important elements regarding literary canonization. The results of the discussion include; (1) canonical literature can be used in the current era of disruption, (2) literary learning is used to find a realm of appreciation for students, (3) literary learning can also be an indoctrination of positive attitudes or values.